2022
DOI: 10.1136/bmjsem-2022-001312
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of idiopathic scoliosis in athletes: a systematic review and meta-analysis

Abstract: ObjectiveThis study aimed to determine the prevalence of idiopathic scoliosis (IS) in child, adolescent and adult athletes of all sports activity levels.DesignSystematic review with meta-analysis.Data sourcesElectronic databases (PubMed, Scopus, ProQuest, Sage journals, ScienceDirect, Google Scholar and Springer) were systematically searched up from inception to 28 September 2021.Eligibility criteria for selecting studiesObservational investigations were included to evaluate the prevalence of IS in athletes (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 64 publications
2
3
1
Order By: Relevance
“…However, some degree of asymmetry is present in all sports, even those considered mostly symmetrical, and each person typically has a dominant side [ 24 ]. Our results support the published findings of elevated scoliosis frequency in swimming [ 9 , 11 ], volleyball [ 11 ], and dancing [ 6 ]. Indeed, volleyball could be considered an asymmetrical sports activity, and even dancing has unilateral loading and high-intensity unilateral movements [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, some degree of asymmetry is present in all sports, even those considered mostly symmetrical, and each person typically has a dominant side [ 24 ]. Our results support the published findings of elevated scoliosis frequency in swimming [ 9 , 11 ], volleyball [ 11 ], and dancing [ 6 ]. Indeed, volleyball could be considered an asymmetrical sports activity, and even dancing has unilateral loading and high-intensity unilateral movements [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…We believe it is mostly due to selection bias, i.e., referral by public opinion or professional advice. We had 321 examinees engaged in gymnastics, and, contrary to the literature [ 6 , 9 , 11 , 25 ], we found no significant association with AIS, despite the putatively long-lasting, asymmetrical loading of the spine [ 25 , 26 ]. Similar to our results, Meyer et al found that scoliosis in gymnasts is associated with higher joint laxity and is not generated by exercise [ 27 ].…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…diopathic scoliosis (IS) is in the spotlight of sports medicine research due to its high prevalence in athletes, and although it is still unknown what sport causes its highest prevalence, a cause-and-effect relationship between this spinal change and sports activity has been cautiously postulated. 1 IS has a long historical record: King Richard III (1452-1485) can be counted among its most famous ancient "patients," as he has been described as being affected by adolescent-onset IS, a condition that likely emerged after he turned 10 without causing him to limp or preventing him from engaging in physical activities. Notably, Richard III was killed at the Battle of Bosworth (August 22, 1485).…”
mentioning
confidence: 99%